Case Study of the Use of Websites and Social Media for SMEs in the CV Bengkel Tas - Deavvy M.R.Y Johassan (Jurnal Komunikasi dan Bisnis, 2026)
SMEs or Small and Medium Enterprises are small and medium-sized businesses that have an important role in the pace of economic development in Indonesia. One of the MSMEs that has existed for a long time in Jakarta is the Small Industry Village (PIK). The Small Industrial Village (PIK) used to be famous and visited by many visitors, before it was eroded by the changing times. The digital era is indeed impossible to avoid, MSME actors must be able to maximize the benefits of digital development. One of the bag craftsman MSMEs that has taken advantage of digital developments is the Central Bengkel Tas. Digital marketing is used to achieve marketing goals through the application of technology and digital media. There are 6 elements in digital marketing , namely interactivity, intelligence, individualization, integration, industry restructuring, and independence of location. The research method used is a qualitative method. The type of research used in this study is descriptive. In conducting this study, the researcher collected various data from various sources using interview techniques, non-participant observations, and documentation. The resource person interviewed by the Researcher was the owner of the Central Bengkel Tas in the Small Industrial Village. The results of the research obtained by UKM Central Bengkel Tas have implemented several elements of digital marketing in  its website. Central Bengkel Tas has implemented two-way communication, regularly changed the content, and expanded its market. However, Central Bengkel Tas is not active in its social media and marketplace. The conclusion of this study is that the implementation and implementation of SME Digital Marketing Central Bengkel Tas is carried out through the website. UKM Central Bengkel Tas also said that the website is one of the tools to market its products and also promotions. Central Bengkel Tas is inactive in its social media and marketplace due to a lack of human resources that makes the owner manage the production part and also the website at once.